A Compendium of Motzkin-Like Path Generating Functions - Jacob Vogelpohl, (The PUMP Journal of Undergraduate Research, 2025)
We catalog fifteen types of Motzkin-like paths with various restrictions and use the symbolic method to determine their generating functions, several of which are new. We also introduce a new type of Motzkin path corresponding to a walk on a circle, rather than on a line.